2014
DOI: 10.1259/bjr.20140367
|View full text |Cite
|
Sign up to set email alerts
|

CT enteroclysis/enterography findings in drug-induced small-bowel damage

Abstract: Objective: To evaluate the CT enteroclysis (CTE)/ enterography findings of patients with small-bowel mucosal damage induced by aspirin or non-steroidal antiinflammatory drugs (NSAIDs) and to compare these findings with the duration of drug use and endoscopic findings. Methods: CTE findings of 11 patients (22 lesions) with drug-induced small-bowel damage were reviewed, including 8 NSAID users and 3 aspirin users. Three patients were short-term users (6 months or shorter) and eight were long-term users (3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, the most common finding of CTE in the present study was contrast enhancement of the intestinal wall, but the positive predictive value of this finding was 56.3%. We previously investigated CTE findings of drug-induced small bowel lesions and classified the contrast enhancement of the intestinal wall into three categories, and we are planning to apply this classification to small bowel intestinal bleeding in the future (30). With regard to the criteria for determining the source of bleeding, when minute lesions, such as type 1a angioectasia, are included as the source of bleeding, the diagnostic yield will increase.…”
Section: Adverse Events Of Cte and Cementioning
confidence: 99%
“…However, the most common finding of CTE in the present study was contrast enhancement of the intestinal wall, but the positive predictive value of this finding was 56.3%. We previously investigated CTE findings of drug-induced small bowel lesions and classified the contrast enhancement of the intestinal wall into three categories, and we are planning to apply this classification to small bowel intestinal bleeding in the future (30). With regard to the criteria for determining the source of bleeding, when minute lesions, such as type 1a angioectasia, are included as the source of bleeding, the diagnostic yield will increase.…”
Section: Adverse Events Of Cte and Cementioning
confidence: 99%
“…The authors classified the findings and their endoscopic correlation in three subsets as depicted in ►Table 2. 37 The circumferential nature of abnormality and often the lack of significant proximal dilatation necessitate the careful orthogonal inspection of bowel and imaging in multiple phases to confirm the presence of stricture. An elaborate discussion on optimal MRE (MR enterography) technique for small bowel imaging is beyond the scope of current review.…”
Section: Ct and Mr Enterography/enteroclysismentioning
confidence: 99%
“…39 Two of eight patients studied by Kishi et al showed mesenteric stranding accompanying mural thickening. 37 Fig. 1 (A) A 60-year-old man presenting with intermittent abdominal pain of a few months' duration.…”
Section: Ct and Mr Enterography/enteroclysismentioning
confidence: 99%